Assessment of postoperative pain and analgesic use in patients undergoing orthopedic surgery - Sharma, Bishnu Dev; Sitaula, Jyoti (Journal of Chitwan Medical College, 2021)
Background: Pain is an unpleasant sensation and occurs frequently in the post-operative period. Pain impairs treatment and recovery of patients and thus should be adequately managed. This study aimed to assess the intensity of pain in the post-operative patients undergoing orthopedic surgery and to evaluate the adequacy of the analgesics used. Methods: This was a prospective observational study conducted at Chitwan Medical College, Department of Orthopedics from May to August 2019. Ninety-six patients who underwent orthopedic surgery were evaluated upto 72 hours after surgery and assessed for pain using interview, Visual Analogue Scale and medical record analysis. Type of analgesic used and its adequacy, using Pain Management Index, were also studied. Results: There were 58 male and 38 female patients with age 18-79 years (mean 38.16 ± 16.34 years). 97.9% patients complained of pain in immediate, 91.7% in 1st and 82.3% in 2nd post-operative period with mean Visual Analogue Scale scores of 6.68, 3.74 and 2.68 respectively. Non-steroidal anti-inflammatory drug was the most frequently prescribed analgesic followed by its combination with opioid. Pain management was inadequate in immediate post-operative (61.5%), but there was significant improvement in 1st and 2nd post-operative period (inadequate Pain Management Index in 28.1% and 12.5% respectively). Conclusions: Most patients experienced pain in the post-operative period, but the intensity decreased as the post-operative hours passed by. Pain management in the immediate post-operative period was inadequate in our study and therefore proper attention should be given to manage pain in the post-operative period.